Anti‐Neoplastic Cytotoxicity of SN‐38‐Loaded PCL/Gelatin Electrospun Composite Nanofiber Scaffolds against Human Glioblastoma Cells In Vitro. Issue 12 (27th October 2015) - Zhu, Xiaodong; Ni, Shilei; Xia, Tongliang; Yao, Qingyu; Li, Haoyuan; Wang, Benlin; Wang, Jiangang; Li, Xingang; Su, Wandong
Abstract : Electrospun poly(ε‐caprolactone) (PCL)/gelatin (GT) scaffolds were developed to provide controlled release of 7‐ethyl‐10‐hydroxy camptothecin (SN‐38). Acetic acid was introduced to improve the miscibility of PCL and GT to produce a homogeneous nanofiber membrane mixture. The effect of SN‐38 content in binary mixtures on processability, fiber morphology, water sorption, swelling, and drug release was investigated. Electrospun PCL/GT blend nonwoven fibers showed fiber surface roughness, decreased PCL crystallinity, and increased swelling with increasing drug content of 1, 2, and 4 wt %. Additionally, increasing the SN‐38 concentration reduced the degradation rate of the GT. Furthermore, we hypothesize the existence of a drug content saturation point in the monoaxial fiber to explain the different drug release patterns of PG2 compared with those of PG1 and PG4. The matrix also showed good biodegradation and anti‐tumor function. Our results demonstrate that SN‐38‐loaded PCL/GT fibers can be obtained by electrospinning. The SN‐38‐loaded fibers merit further evaluation as a means to potentially prevent locoregional recurrence following surgical tumor resection. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4345–4354, 2015